Diorchis pelagicus sp.nov. (Cestoda: Hymenolepididae) from the Whiskered Auklet, Aethia pygmaea , and the Crested Auklet, A . cristatella , in the Western Aleutian Islands, Alaska - Hoberg, Eric P. (Canadian Journal of Zoology, 1982)
Diorchis pelagicus sp.nov. (Cestoda: Hymenolepididae) is described from whiskered auklets, Aethia pygmaea (Gmelin), and reported from a crested auklet, A. cristatella (Pallas), in Alaska. The species can be distinguished from others of the genus Diorchis Clerc, 1903 by the small size of the scolex (armed with 10 hooks, 35–41 μm in length), strobila, and most internal organs. A combination of characters including suckers without spines, a relatively long cirrus sac, a cylindrical cirrus lacking a basal bulb and armed with 12–20 longitudinal rows of minute spines measuring 1–2 μm, a globular to bilobed ovary, and ovoid eggs without filaments further distinguish this species from its congeners. In addition, the longitudinal musculature of the cirrus sac appears to be unique for members of the genus. This is the first report of cestodes of the genus Diorchis from pelagic seabirds, and is the first record of any cestode from birds of the genus Aethia Merrem.